The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/nvsm.214
|View full text |Cite
|
Sign up to set email alerts
|

The marketing effectiveness of UK environmental charity websites compared to best practice

Abstract: All nonprofit organisations need to give attention to their marketing strategies in order to maximise the funding and support they receive and the numbers using their services. The web offers a new communications medium with which to achieve this. This paper compares suggested best practice approaches to web marketing using the websites of UK environmental charities as a type of nonprofit organisation. Copyright © 2003 Henry Stewart Publications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 3 publications
(2 reference statements)
1
34
0
1
Order By: Relevance
“…However, although the organizational employees are often passionate about their NPO's cause, they often lack business experience or long-term objectives (Bissell, 2003). Citing Akchin (2001), Wenham et al (2003) suggest that NPOs lack a customer orientation in their marketing practices, and few embrace a marketing approach to their marketing operations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although the organizational employees are often passionate about their NPO's cause, they often lack business experience or long-term objectives (Bissell, 2003). Citing Akchin (2001), Wenham et al (2003) suggest that NPOs lack a customer orientation in their marketing practices, and few embrace a marketing approach to their marketing operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another major failure of NPO's Internet use was poor ''capture efficiency'', or the failure of search engines to return the NPO's Web site near the top of the search list (Wenham et al, 2003). However, to resolve this, the NPO need only ensure the proper registration of a Web site with these search engines (Hart, 2002).…”
Section: A Special Note On Internet Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the study 1 results, and what others who have examined charity web sites have reported (e.g. Sargeant, 2001;Sargeant and Jay, 2003;Wenham et al, 2003;Goatman and Lewis, 2007), it appears that most charity web sites are designed merely for what Rowley (2001) terms 'contact' purposes.…”
Section: Discussionmentioning
confidence: 82%
“…The increase in online fundraising may be due to aid agencies designing their websites based on the developing literature on aid agency web site design (e.g. Fox and Carr, 2000;Gueguen and Jacob, 2001;Sargeant, 2001;Wenham et al, 2003;Powell, 2005;Goatman and Lewis, 2007;Sargeant et al, 2007;Waters, 2007;Richard, 2008;Burt and Dunham, 2009;McWah and Carr, 2009). One issue, which is apparent in this literature and also in the e-commerce literature in general (e.g.…”
Section: Introductionmentioning
confidence: 96%